Information management and knowledge sharing in supply chains operating in Brazil. (1st January 2013) - Maçada, Antônio Carlos Gastaud; Costa, Jaciane Cristina; Oliveira, Mírian; Curado, Carla
This article seeks to answer the following research question: how do enterprises within an automotive supply chain manage inter-organisational information and share knowledge? To this end, this study offers an analysis of the state of the inter-organisational information management and knowledge sharing in a supply chain in the Brazilian automotive sector. The research follows a qualitative approach. The study revisits models by Davenport (1997) and Dyer and Nobeoka (2000) aimed to incorporate particularities from the supply chain analysis by conducting a case study in the Brazilian automotive sector. Information exchanged and knowledge shared within the automotive chain is basically operational in nature and the phenomena occur at layers: unilaterally, bilaterally and multilaterally. Power and technology are elements that need to be balanced to achieve the effective management of inter-organisational information management and knowledge sharing. This paper highlights the relation between information management and knowledge sharing in an automotive supply chain.